Paediatric neurorehabilitation: finding and filling the gaps through the use of the Institute for Manufacturing strategic roadmapping method. Issue 3 (2nd September 2017) - Hamilton, Colin; Maw, Anna; Gill, Andrew; Brahmbhatt, Mita; Phaal, Robert; Pickard, John
Abstract : Introduction: Acquired brain injury (ABI) is a major cause of morbidity and mortality in childhood. Specialist rehabilitation services are often situated far from families and local services may be non-standardised and fragmented. A strategic level of understanding is needed to improve patient care and outcomes. Roadmapping techniques are commonly used in industry settings to discover and present a systematic understanding of structures; however, they are rarely used in the healthcare setting. With continuing pressures on healthcare systems worldwide, they provide an effective method for examining services. Methods: The Institute for Manufacturing (IfM) strategic roadmapping method was used to identify areas of difficulty and opportunities in paediatric neurorehabilitation. Participants included stakeholders from a wide range of professions and sectors who have input with children after ABI. Results: Delegates identified a range of 'layers' covering trends, drivers, current experience and unmet needs. From these layers, four priorities were identified and further expanded.These included: 'access to medical and therapy expertise close(r) to home', 'shared understanding across family, school and health', 'family and professional awareness of resources and support' and 'establishing a centre for rehabilitation technology evaluation, advice and co-ordination of services and research'. Conclusion: The IfM strategic roadmapping method identified and developed key areas for development in the field of paediatric neurological rehabilitation. Healthcare professionals looking at strategic level difficulties should strongly consider the use of such systematic tools when evaluating areas of practice.